(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. Nephrotic syndrome (NS), a common chronic pediatrickidney disease, is associated with immune system dysfunction.The exact role of MIF -137 G>C gene polymorphism on risk of NSis not clear. The current study aimed to evaluate the relationshipbetween MIF -173 G>C (rs755622) variant and susceptibility to NS.Methods. This case-control study conducted on 134 children withNS and 141 healthy children. Extraction of genomic DNA fromwhole blood was done using salting out method. Genotyping ofthe MIF -173 G>C polymorphism was performed using polymerasechain reaction restriction fragment length polymorphism (PCRRFLP)method.Results. The findings showed that MIF -173 G>C variant significantlyincreases the risk of NS in codominant (OR = 1.82, 95%CI = 1.08-3.08, P = 0.026, GC vs GG), dominant (OR = 1.90, 95%CI = 1.14-3.16,P = 0.015, GC+CC vs GG), overdominant (OR = 1.75, 95%CI = 1.04-2.94, P = 0.037, GC vs GG+CC) and allele (OR = 1.76, 95%CI = 1.13-2.74, P = 0.014, C vs G) inheritance models. Stratified analysisperformed by sex and response to treatment. The findings revealedthat this variant was associated with increased risk of NS in male.No correlation between the variant and response to treatment wasfound.Conclusion. In summary, the results indicated that MIF -137 G>Cis significantly associated with increased risk of NS. More studieswith larger sample size among different ethnicities are needed toverify our findings.